Zinc finger protein 384 (ZNF384) impact on childhood mixed phenotype acute leukemia and B-cell precursor acute lymphoblastic leukemia. Issue 12 (15th October 2022) - Sudutan, Tugce; Erbilgin, Yucel; Hatirnaz Ng, Ozden; Karaman, Serap; Karakas, Zeynep; Kucukcankurt, Fulya; Celkan, Tiraje; Timur, Cetin; Ozdemir, Gul Nihal; Hacısalihoglu, Sadan; Gelen, Sema Aylan; Sayitoğlu, Müge
Abstract: B-cell precursor acute lymphoblastic leukemia (BCP-ALL) is a heterogeneous malignancy and consists of several genetic abnormalities. Some of these abnormalities are used in clinics for risk calculation and treatment decisions. Patients with ZNF384 rearrangements had a distinct expression profile regardless of their diagnosis, BCP-ALL or mixed phenotype acute leukemia (MPAL) and defined as a new subtype of ALL. In this study, we screened 42 MPAL and 91 BCP-ALL patients for the most common ZNF384 fusions; Z NF384::TCF3, ZNF384::EP300 and ZNF384::TAF15 by using PCR. We identified ZNF384 fusions in 9.5% of MPAL and 7.6% of BCP-ALL. A novel breakpoint was identified in ZNF384::TCF3 fusion in one BCP-ALL patient. T-myeloid MPAL patients showed significantly lower ZNF384 expression compared to lymphoid groups. Patients with ZNF384 r had intermediate survival rates based on other subtypes. Prognostic and patient-specific treatment evaluation of ZNF384 fusions in both ALL and MPAL might help to improve risk characterization of patients.